Global alignment of immunization safety assessment in pregnancy – The GAIA project. Issue 49 (1st December 2016) - Bonhoeffer, Jan; Kochhar, Sonali; Hirschfeld, Steven; Heath, Paul T.; Jones, Christine E.; Bauwens, Jorgen; Honrado, Ángel; Heininger, Ulrich; Muñoz, Flor M.; Eckert, Linda; Steinhoff, Mark; Black, Steven; et al.
Abstract: Immunization in pregnancy provides a promising contribution to globally reducing neonatal and under-five childhood mortality and morbidity. Thorough assessment of benefits and risks for the primarily healthy pregnant women and their unborn babies is required. The GAIA project was formed in response to the call of the World Health Organization for a globally concerted approach to actively monitor the safety of vaccines and immunization in pregnancy programs. GAIA aims to improve the quality of outcome data from clinical vaccine trials in pregnant women with a specific focus on the needs and requirements for safety monitoring in LMIC. In the first year of the project, a large and functional network of experts was created. The first outputs include a guidance document for clinical trials of immunization in pregnancy, a basic data collection guide, ten case definitions of key obstetric and neonatal health outcomes, an ontology of key terms and a map of pertinent disease codes. The GAIA Network is designed as an open and growing forum for professionals sharing the GAIA vision and aim. Based on the initial achievements, tools and services are developed to support investigators and strengthen immunization in pregnancy programs with specific focus on LMIC.